Teaching English in Cuban Higher Education - Delgado-Fernández, Leandro; Puerto-Valdés , Adis Eliany (Educación y sociedad, 2024)
In Cuban Higher Education, English language teaching plays an important role in the comprehensive training of future professionals, helping them acquit in the different sectors of the society. The major – Bachelor of Education, Foreign Languages, English – qualifies English language professionals to carry out the teaching-learning process of the English language in the different educational contexts, and for that, the subject Didactics of Foreign Languages is imparted. In this article, the authors aim to explore the dialectical relationship between the triad – English, didactics and higher education. During the exploratory phase, methods and techniques of the empirical level were used, such as document analysis, observation and interview. Deepening on the didactic aspects that the professor must take into account in the teaching of the English language, a contradiction was spotted – the English language policy based on the Common European Framework of Reference for Languages is implemented in the training of professionals with a non-philologist profile while it is not in those with a philologist profile, i.e., English teachers-to-be.